울산지역 유통 발효주의 잔류농약 및 중금속 실태조사 - 김희정; 김경진; 김민경; 김금비; 김수희; 조영경; 박주은; 정소연; 서원덕; 최영선; Hee-Jung Kim; Kyoung-Jin Kim; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2024)
발효주의 잔류물질 실태조사를 위해 울산지역에서 유통 되는 발효주 150건을 수거하여 잔류농약 400종과 중금속 납, 카드뮴, 수은을 분석하였다. 잔류농약 분석 결과, 102 건(68%)의 검출을 나타냈으며 검출된 농약 종류는 35종 으로 그 중 원료 농산물의 기준이 없는 농약은 4종이 검 출되었다. 발효주 종류별로 비교하면 와인이 60건의 검사 중 54건(90%)으로 가장 많은 잔류농약이 검출되었고 맥 주는 60건 중 37건(61.7%), 막걸리는 30건 중 11건(36.7%) 이 검출되었다. 발효주에 대한 중금속 분석 결과는 납 73 건(48.7%), 카드뮴은 9건(6.0%), 수은은 36건(24.0%)을 나 타내었다. 납은 73건의 검출 중 와인이 57건(78.1%)을 차 지해 가장 높은 검출을 나타내었고 카드뮴과 수은은 검출 된 9건, 36건 중 막걸리가 7건(77.8%), 13건(36.1%)으로 가장 많이 검출되었다. 각 품목에서 검출된 잔류농약 및 중금속 항목에 대해 인체노출량 평가결과는 모두 1% 미 만으로 안전한 것으로 나타났다. In this study, we investigated in pesticide residues and heavy metals in fermented liquor products (wine, beer, makgeolli). Targeted analysis of 400 pesticide residues in the sample was performed using the quick, easy, cheap, effective, rugged, and safe (QuEChERS) extraction method, followed by gas chromatography-tandem mass spectrometry (MS/MS) and LC-MS/MS. The contents of heavy metals (Pb, Cd) were determined by ICP-MS using the microwave method. The mercury was measured using a mercury analyzer. From the analysis of 150 cases, 102 (68.0%) cases of fermented liquor were detected, and 35 pesticide residues (including metalaxyl, mandipropamid, azoxystrobin, and fenhexamid) were detected among the 400 pesticide residues tested. Pb, Cd, and Hg were tested in 150 samples. Lead was detected in 73 samples (48.7%), cadmium in 9 samples (6.0%), and mercury in 36 samples (24.0%). Exposure assessment was conducted to determine the safety of the detected pesticide residues and heavy metals. According to this assessment, the pesticide residues and heavy metals showed very low %ADI values (less than 1%).